Improving Time to Molecular Testing Results in Patients With Newly Diagnosed, Metastatic Non–Small-Cell Lung Cancer. Issue 11 (3rd November 2022) - Ossowski, Stephanie; Neeman, Elad; Borden, Charles; Stram, Douglas; Giraldo, Lucy; Kotak, Dinesh; Thomas, Sachdev; Suga, J. Marie; Lin, Amy; Liu, Raymond
Abstract : PURPOSE: Next-generation sequencing (NGS) is a crucial component of evaluation of patients with newly diagnosed metastatic non–small-cell lung cancer (NSCLC) to determine appropriate first-line treatment. This quality improvement project aimed to reduce time to NGS results in patients with metastatic NSCLC. METHODS: We reviewed electronic medical records of patients with newly diagnosed, untreated metastatic NSCLC from December 2018 to August 2021 and determined the number of days from pathologic diagnosis to NGS results. We reviewed process maps for oncology, pathology, the Division of Research, and a NGS vendor to determine factors leading to preventable delays. Since November 2020, we created an automated, electronic weekly report to provide earlier identification of new pathologic diagnoses in patients with metastatic NSCLC. On June 2021, we worked with our NGS vendors to expand days of the week to accept specimens. RESULTS: Our interventions reduced the median time from pathologic diagnosis to NGS results from 24 (standard deviation [SD] 9) to 16 (SD 6) days. The median time from biopsy results to NGS order was reduced from 7 days to 1 day. The time from the specimen being sent from pathology to the NGS vendor was a median of 6 days in both cohorts. The total time from pathologic diagnosis to appropriate treatment was reduced from 33 (SD 18) to 22 (SD 8) days. CONCLUSION: NGS processing in a community setting can be complex. Using a systems focused approach to quality improvement is crucial in identifying the greatest barriers in an organization. We found that delays in time to NGS results can be reduced by improved communication and workflows among departments.